Micro venture capital - Amore, Mario Daniele; Pelucco, Valerio; Conti, Annamaria (John Wiley and Sons Inc, 2023)
Research Summary: Recently,the venture capital (VC) industry has experienced the entry of several new capital providers. Using US data on investors and their portfolio startups from 2000 to 2022,we document the emergence of a new type of investors: the micro VC. Our analysis reveals that micro Venture Capitalists (VCs) have an idiosyncratic investment strategy,which differs from traditional VCs. Compared with these investors,micro VCs invest in riskier startups,that is,early-stage ventures initiated by less experienced founders; yet,micro VCs are less likely to syndicate,stage their investments,and replace the startup founders. Additionally,startups funded by micro VCs are less likely to experience successful exits than those backed by traditional VCs. These results can be traced to a mix of smaller capital endowments,less sophisticated limited partners,and lesser human capital of which micro VCs dispose,and that may induce them to spread their thin capital across many investments to maximize returns. Our analysis also uncovers important differences in the strategies pursued by micro VCs and business angels. Managerial Summary: The VC industry is increasingly populated by a variety of investors with disparate characteristics and objectives. One such type of investors is represented by the so-called micro VC firms. These are VC firms that manage funds typically below $50 million and focused primarily on investing in founder-led startups. We leverage comprehensive VC data in the United States to answer three questions: (1) Who leads micro VC firms? (2) How do micro VC firms invest? (3) How do startups backed by micro VC perform? We find that micro VC firms are often led by relatively inexperienced entrepreneurs with little VC experience,and these firms are supported by less sophisticated limited partners. Although micro VC firms invest in riskier startups,they are less engaged in syndication and investment staging than traditional VC firms. Finally,micro VC-backed startups have a lower probability of successful exit as compared with those backed by traditional VC firms. Collectively,our results suggest that micro VCs differ from traditional VCs beyond being “micro.”. © 2023 The Authors. Strategic Entrepreneurship Journal published by John Wiley & Sons Ltd on behalf of Strategic Management Society.
Keywords: (Micro) venture capital; Early-stage investment; Fund size; Performance; Startup; 53 Ciencias Económicas::5306 Economía del cambio tecnológico; ODS 8 - Trabajo decente y crecimiento económico; ODS 9 - Industria, innovación e infraestructura